MF-Net: Multi-Scale Information Fusion Network for CNV Segmentation in Retinal OCT Images - Meng, Qingquan; Wang, Lianyu; Wang, Tingting; Wang, Meng; Zhu, Weifang; Shi, Fei; Chen, Zhongyue; Chen, Xinjian (Frontiers in Neuroscience, 2021)
Choroid neovascularization (CNV) is one of blinding ophthalmologic diseases. It is mainly caused by new blood vessels growing in choroid and penetrating the Bruch’s membrane. Accurate segmentation of CNV is essential for ophthalmologists to analyze the patient's condition and specify treatment plan. Although many deep learning based methods have achieved promising results in many medical image segmentation tasks, CNV segmentation in retinal OCT images is still very challenging as the blur boundary of CNV, large morphological differences, speckle noise and other similar diseases interference. In addition, the lack of pixel-level annotation data is also one of factors that affect the further improvement of CNV segmentation accuracy. To improve the accuracy of CNV segmentation, a novel multi-scale information fusion network (MF-Net) based on U-Shape architecture is proposed for CNV segmentation in retinal OCT images. A novel multi-scale adaptive-aware deformation module (MAD) is designed and inserted into the top of encoder path, aiming at guiding the model to focus on multi-scale deformation of the targets and aggregates the contextual information. Meanwhile, to improve the network’s ability to learn to supplement low-level local high resolution semantic information to high-level feature maps, a novel semantics-details aggregation module (SDA) between encoder and decoder is proposed. In addition, to leverage unlabeled data to further improve the CNV segmentation, a semi-supervised version of MF-Net is designed based on pseudo label data augmentation strategy, which can leverage unlabeled data to further improve CNV segmentation accuracy. Finally, comprehensive experiments are conducted to validate the performance of the proposed MF-Net and SemiMF-Net. The experiment results show that both proposed MF-Net and SemiMF-Net outperforms other state-of-the-art algorithms.